Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Ipas Siswa Kelas V SDN Sendangguwo 01 - Fita Ulya; Aries Tika; Noor Miyono; Evi Ariestanti (Departement of Mathematics Education, 2024)
This research focuses on the influence of learning models on improving student learning outcomes. Lack of teacher variation and innovation in teaching and lack of use of sources and media. The learning that is taking place now is included at the elementary school level, especially in Natural and Social Sciences (IPAS) subjects. The main aim of the research carried out was to determine the effect of the problem based learning model on student learning outcomes. In this research the author used a Pre-Experimental Design research type with One Group Pretest Posttest type. The sample used was 27 class V students at SDN Sendangguwo 01. The results of the research that had been tested for normality in the pretest and posttest were normally distributed. Judging from the SPSS output pretest results and the sig column. which has a value of 0.193 > α (0.05) which means the data is normally distributed. From the SPSS output posttest results in the sig column. which has a value of 0.211 > α (0.05) which means the data is normal. From the results of the paired sample t-test, the results show sig. (2-tailed) 0.000. If sig. (2-tailed) 0.000 < α (0.05) then Ha is accepted, which means there is an influence of the problem based learning model on students' critical thinking abilities and in the Normalized Gain test based on what has been calculated using SPSS 26, the integrated results are tall